Electrocortical activity associated with subjective communication with the deceased - Delorme, Arnaud; Beischel, Julie; Michel, Leena; Boccuzzi, Mark; Radin, Dean; Mills, Paul (Frontiers in Psychology, 2013)
During advanced meditative practices, unusual perceptions can arise including the sense of receiving information about unknown people who are deceased (“discarnates”). The reported experience of initiating mental communication with the deceased, may involve a state of consciousness similar to that achieved in contemplative meditation practices. As with meditation, this mental state involves calming mental chatter and becoming receptive to subtle feelings and sensations. Psychometric and brain electrophysiology data were collected from six individuals who had previously reported accurate information about discarnates under double-blind conditions. Each experimental participant performed two tasks with eyes closed. In the first task, the participant was given only the first name of a discarnate and asked 25 questions. After each question, the participant was asked to silently perceive information relevant to the question for 20 seconds so clean electro-encephalography data could be collected and then respond verbally. Responses were then transcribed and scored by individuals who knew the discarnates. Of the six participants, two could not be evaluated, and the four other participants scored higher than chance level (p<0.03 for 3 of the 4 participants). The correlation between accuracy and brain activity was significant in frontal theta for one participant (p < 0.01). In the second task, participants were asked to experience four mental states, each repeated three times for one minute: (1) Thinking about a known living person, (2) Listening to a biography, (3) Thinking about an imaginary person, and (4) Interacting mentally with a known discarnate. Statistically significant differences in electrocortical activity among the four conditions were obtained in all six participants, primarily at gamma frequencies. These differences suggest that the impression of communicating with the deceased may be a distinct mental state distinct from ordinary thinking or imagination.